2019
DOI: 10.3389/fcvm.2019.00072
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Assessment of Cardiac Valve Substitutes: Current Status and Considerations for Engineered Tissue Heart Valves

Abstract: Tissue engineered heart valve (TEHV) technology may overcome deficiencies of existing available heart valve substitutes. The pathway by which TEHVs will undergo development and regulatory approval has several challenges. In this communication, we review: (1) the regulatory framework for regulation of medical devices in general and substitute heart valves in particular; (2) the special challenges of preclinical testing using animal models for TEHV, emphasizing the International Standards Organization (ISO) guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Three key functional parameters, i.e., EOA, pressure gradient, and peak jet velocity, were calculated to assess the hydrodynamic performances of BHV. All three parameters are important indicators for the clinical assessment of aortic valve stenosis severity 28,[59][60][61] . Although the baseline hydrodynamic performances of unimplanted BHV in pulse simulators have been repeatedly reported [62][63][64] , to the best of our knowledge, we are the first to evaluate the hydrodynamic performances of BHV following in vitro incubations that simulate AGE formation observed in clinical explants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three key functional parameters, i.e., EOA, pressure gradient, and peak jet velocity, were calculated to assess the hydrodynamic performances of BHV. All three parameters are important indicators for the clinical assessment of aortic valve stenosis severity 28,[59][60][61] . Although the baseline hydrodynamic performances of unimplanted BHV in pulse simulators have been repeatedly reported [62][63][64] , to the best of our knowledge, we are the first to evaluate the hydrodynamic performances of BHV following in vitro incubations that simulate AGE formation observed in clinical explants.…”
Section: Discussionmentioning
confidence: 99%
“…The pressure was adjusted via the Systemic Mean Pressure Control knob. All BHVs were subjected to physiological conditions for the aortic position as per ISO-5840 28 and FDA Replacement Heart Valve Guidance (heart rate at 70 BPM; temperature at 37°C; flow rate at 5L/min; Systolic and diastolic pressures at 110/80 ± 5 mmHg; mean pressure at 95 ± 5 mmHg; systolic duration at 35 ± 5%). Flow, ventricle pressure, and aortic pressure were measured using a transonic sensor (Transonic Systems, Ithaca, NY, USA) and pressure sensors (BDC Laboratories), respectively 29 .…”
Section: Patient Population (Supplementalmentioning
confidence: 99%
“…Heart valve prosthesis are designated as high-risk medical devices, requiring rigorous in-vitro and in-vivo safety, efficacy and/or performance studies 24 . The use of standardized animal models for preclinical testing is thereby essential to provide invaluable information on the device safety.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a tissue engineered heart valve (TEHV) created from an individual’s own cells with the ability to grow, repair, and remodel offers a potential solution to this problem. Significant progress has been made including the performance of the first clinical trials evaluating the safety of this technology [ 150 , 151 , 152 ]. Unfortunately, the preliminary results of these trials have demonstrated some significant valve-related complications that have prevented their widespread use, most notably leaflet retraction which leads to regurgitation.…”
Section: Ecm and Therapeuticsmentioning
confidence: 99%